ANALISIS JARAK GRID HARDFACING TERHADAP NILAI KEKUATAN BENDING PADA MATERIAL ASTM A36: Hardfacing - Awali, Jatmoko; Dewanto, Hizkia Alpha; Ismail , Andi Idhil (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Welding is the joining of metals in liquid form using heat energy in making products in the process of joining materials such as in the automotive sector. The development of welding has reached the additive manufacturing process, one of which is hardfacing, namely the thickening of a component that already exists in the industrial sector. In the automotive sector, many people use ASTM A36 or mild steel, namely carbon steel, for standard specifications for structural applications. Hardfacing is a process with an angle welding approach and the resulting structure has a direct relationship with the welding parameters and material characteristics during welding. Adding corner welding grids to increase the strength value of special mechanical properties such as car bodies. This research aims to determine the effect of the shape of the welding grid on the mechanical properties of GMAW welding using ER70S-6 electrodes and a welding current of 80 Ampere with variations in the weld metal spacing, namely 5 mm, 10 mm, 15 mm, and with ASTM A 36 material with a thickness of 2 mm. GMAW welding uses constant current by varying the hardfacing grid. From the research results it is known that the largest stiffness value is found at a variation of the weld metal distance of 10 mm with an average value of 1737.5 N. In the microstructure the phase formed is ferrite (F) and along the grain boundaries pearlite (P) is formed.